KEMAMPUAN BERPIKIR KRITIS SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN BRAIN BASED LEARNING - Binti Anisaul Khasanah; Indah Dwi Ayu (Universitas Muhammadiyah Kotabumi, 2017)
The purpose of this study is how student’s critical thinking skills through the application of Brain Based Learning model. The population in this study were all students of class VII even semester SMP Muhammadiyah 1 Gadingrejo academic year 2016-2017 which amounted to 184 students and divided into 5 classes. Sampling technique used in determining the sample is cluster random sampling. Analysis of the data used is to make the percentage of achievement of critical thinking skills according to indicators measured. The results of this study are 1) students who achieve the ability to formulate the principal issues where students are asked to determine what is known and what is asked and the correct counting operation is 81.82%; 2) students who achieve the ability to determine the consequences of a provision taken where students provide a systematic answer related questions given at 75.76%; 3) students who achieve the ability to determine the solution with some solutions where students are asked to provide solutions to answer more than one of the given problem of 79.41%; 4) students who achieve the ability to disclose data / definitions / theorems in solving problems where students are asked to prove the truth of a given statement of 82.35% and 5) students who achieve the ability to evaluate the relevant argument in the settlement of a problem in which the student is required to complete problem solving problem equal to 76,47%.